2016
DOI: 10.1038/mtna.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-miRNA-212 Conjugate Sensitizes NSCLC Cells to TRAIL

Abstract: TNF-related apoptosis-inducing ligand (TRAIL) is a promising antitumor agent for its remarkable ability to selectively induce apoptosis in cancer cells, without affecting the viability of healthy bystander cells. The TRAIL tumor suppressor pathway is deregulated in many human malignancies including lung cancer. In human non-small cell lung cancer (NSCLC) cells, sensitization to TRAIL therapy can be restored by increasing the expression levels of the tumor suppressor microRNA-212 (miR-212) leading to inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 57 publications
1
48
0
Order By: Relevance
“…More importantly, following axl-148b conjugate administration into mouse xenotransplants, increased tumor necrosis and apoptosis were observed in the primary masses, together with a strong reduction of CTCs and metastasis formation in distant organs. The chimeric axl-148b molecule used in our investigation resulted highly specific for AXL + cells, similarly to what observed here or previously for GL21.T [18][19][20]25]. In fact, treatments with axl-148b conjugate allowed an efficient increase of miR-148b in AXL + but not in AXLcells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…More importantly, following axl-148b conjugate administration into mouse xenotransplants, increased tumor necrosis and apoptosis were observed in the primary masses, together with a strong reduction of CTCs and metastasis formation in distant organs. The chimeric axl-148b molecule used in our investigation resulted highly specific for AXL + cells, similarly to what observed here or previously for GL21.T [18][19][20]25]. In fact, treatments with axl-148b conjugate allowed an efficient increase of miR-148b in AXL + but not in AXLcells.…”
Section: Discussionsupporting
confidence: 85%
“…However, apart from acting on their targets, aptamers can be used as carriers to convey therapeutic tools (chemotherapy drugs, siRNAs and miRNAs) to cells in a specific manner [13][14][15][16][17]. Since most tumor cells overexpress AXL, a tyrosine kinase receptor with oncogenic functions, an RNA aptamer against AXL, GL21.T, has been developed and used to block AXL downstream signaling [18] and to selectively deliver small non-coding RNAs [19][20][21]. In our work, we conjugated miR-148b to GL21.T to generate an axl-miR-148b conjugate or chimeric aptamer (from now on, briefly called axl-148b), and obtained a specific increase of miR-148b in treated AXL-expressing cells with the consequent silencing of ALCAM and ITGA5, two miR-148b direct targets.…”
Section: Ivyspringmentioning
confidence: 99%
“…Recent evidence showed that the technique of targeted gene expression, including specific gene-promoter-operating expression and distinct delivery systems, is a crucial strategy for gene therapy against various cancers including lung cancer 4, 5, 6, 7. And, microRNAs (miRNAs), which are endogenous 21- to 23-nt non-coding RNAs, have pointed to central regulatory roles in the development of lung cancer and emerged as important targets for gene therapy against clinical lung cancer 8, 9, 10, 11. This research suggested that targeted expression of distinct miRNA molecules might be a useful therapeutic strategy for lung cancer, which would be ultimately benefit to the outcome of clinical lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers are suitable for targeting as they are noncytotoxic, non‐immunogenic, with superior tissue penetration, easy to modify and cheap . Conjugation of miRNAs to aptamers has been used to specifically target the nucleic acid to cells expressing the ligands recognized by the aptamer . Conjugation to cell‐penetrating peptides enables crossing of cell and endosomal membranes.…”
Section: The Utility Of Mirnas As New Therapeutic Targetsmentioning
confidence: 99%